Enantioselective construction of cis -hydroindole scaffolds via an asymmetric inverse-electron-demand Diels–Alder reaction: application to the formal total synthesis of (+)-minovincine - Zhang, Fangqing; Ren, Bing-Tao; Zhou, Yuqiao; Liu, Yangbin; Feng, Xiaoming (Chemical science (Cambridge), 2022)
cis -Hydroindole scaffolds widely exist in a large number of natural products, pharmaceuticals, and organocatalysts. Therefore, the development of efficient and enantioselective methods for the construction of cis -hydroindoles is of great interest and importance. Herein, a novel approach for the enantioselective synthesis of cis -hydroindole scaffolds has been realized through a chiral N , N ′-dioxide/Mg(OTf) 2 complex catalyzed asymmetric inverse-electron-demand Diels–Alder (IEDDA) reaction of 2-pyrones and cyclic enamines. A series of substituted cis -hydroindole derivatives bearing multiple contiguous stereocenters and functional groups were obtained in good to excellent yields and enantioselectivities (up to 99% yield, and 95% ee) under mild reaction conditions. Moreover, the enantioselective formal total synthesis of (+)-minovincine was concisely furnished with high efficiency and stereoselectivity to demonstrate the synthetic potential of this method.